PENGARUH PENGENDALIAN KUALITAS (QUALITY CONTROL) TERHADAP KUALITAS PRODUKPADA PT. BENTARA SINAR PRIMA - Dimas Muhamad Supeno, - (2011)
Quality product is important for a company, therefore the company has many important roles to maintain product quality. Companies need to out the right way to continue product quality to always compete with other companies to want exist both from within the country or from the other countury. Required quality control is good so the company can ensure that the goods produced are of quality goods. There are problems in the quality level of products such as fabric elasticity that is still not in accordance with the sample of firms, results are not maximum cutting cloth, fabric elasticity endurance is still low and so forth. The purpose of this study were (1) To know the description of quality control at PT. Bentara Sinar Prima, (2) To know the illustration quality of the product at PT. Bentara Sinar Prima, and (3) To determine the effect of quality control the quality of the PT. Sinar Prima Bentara The research method is descriptive analysis method with survey techniques with large samples is 30 respondents, subjects in this study are employees of PT. Sinar Prima Bentara quality control division. The independent variable is the quality control and the dependent variable is the quality of the product. The data analysis technique used is simple linear regression analysis and product moment correlation coefficient. The results obtained give the conclusion that the quality control (quality control) at PT. Bentara Sinar Prima is in both categories and the picture quality of the products are also in both categories. The result of calculating the correlation of 0.686, meaning that there is a strong relationship between quality control with a quality product. Simple calculation results obtained regesi analysis equation Y = 15.493 +0.817 X and KD = 47.10% means that the product quality is affected by quality control of 47.10% while the remaining 52.9% is influenced by other factors that are not in perusal.